The MUDDLED PANCYTOPENIA - Umakanthan, K.; Riaz, Juhi; Sundari, Mohana (Indian Journal of Case Reports, 2022)
Pancytopenia, always remains a challenge for its detailed diagnostics evaluation, ranging from Megaloblastic Anemia to  Marrow aplasia and leukemias. Here, we report the case scenario of a 70 year old male who presented with pancytopenia and his elaborated diagnostics approach, concluding the diagnosis of myelofibrosis with positive W515L. This case illustrates the uniqueness of establishing the diagnosis of myelofibrosis.